Snapdragons: the chatterbox turtle - Rider, Cynthia; Petrlik, Andrea (Oxford University Press UK, 2004)
Turtle loves to talk to the animals. But when two geese offer to fly him to their beautiful lake, Turtle must hold tightly to the stick with his mouth as they carry him. He remembers not to answer the parrots and the monkey, but what will happen when Snake taunts him?